Contrast-Enhanced Magnetic Resonance Angiography Using a Novel Elastin-Specific Molecular Probe in an Experimental Animal Model - Reimann, Carolin; Brangsch, Julia; Kaufmann, Jan Ole; Adams, Lisa C.; Onthank, David C.; Robinson, Simon P.; Botnar, Rene M.; Collettini, Federico; Makowski, Marcus R. (Contrast Media & Molecular Imaging, 2018)
Objectives. The aim of this study was to test the potential of a new elastin-specific molecular agent for the performance of contrast-enhanced first-pass and 3D magnetic resonance angiography (MRA), compared to a clinically used extravascular contrast agent (gadobutrol) and based on clinical MR sequences. Materials and Methods. Eight C57BL/6J mice (BL6, male, aged 10 weeks) underwent a contrast-enhanced first-pass and 3D MR angiography (MRA) of the aorta and its main branches. All examinations were on a clinical 3 Tesla MR system (Siemens Healthcare, Erlangen, Germany). The clinical dose of 0.1 mmol/kg was administered in both probes. First, a time-resolved MRA (TWIST) was acquired during the first-pass to assess the arrival and washout of the contrast agent bolus. Subsequently, a high-resolution 3D MRA sequence (3D T1 FLASH) was acquired. Signal-to-noise ratios (SNRs) and contrast-to-noise ratios (CNRs) were calculated for all sequences. Results. The elastin-specific MR probe and the extravascular imaging agent (gadobutrol) enable high-quality MR angiograms in all animals. During the first-pass, the probes demonstrated a comparable peak enhancement (300.6 ± 32.9 vs. 288.5 ± 33.1, p>0.05). Following the bolus phase, both agents showed a comparable intravascular enhancement (SNR: 106.7 ± 11 vs. 102.3 ± 5.3; CNR 64.5 ± 7.4 vs. 61.1 ± 7.2, p>0.05). Both agents resulted in a high image quality with no statistical difference (p>0.05). Conclusion. The novel elastin-specific molecular probe enables the performance of first-pass and late 3D MR angiography with an intravascular contrast enhancement and image quality comparable to a clinically used extravascular contrast agent.
CRIS-Team Scopus Importer:2023-03-08